Deporte y educación: cómo desarrollar una carrera dual adecuada - Rodrigues da Costa, F.; Scremin de Miranda, I.; Figueiredo, A. J. (Cultura, Ciencia y Deporte, 2021)
This study aimed at analyzing the legislation on High Performance Sports (HPS) and educational training in Brazil under the concept of Dual Career (DC). Through a documentary analysis, reflection questions about a national sports project capable of supporting the successful conciliation between sports and school/ academic training in dual career dynamics were raised. Since the Constitution ensures equal conditions for access and continuation of education, clarity and understanding about the HPS development process and its demands regarding the conciliation with school/ academic training is necessary. The analysis of the legislation in force in Brazil shows that student-athletes are not supported and that although some proposals in progress are advancing, they do not fully address the needs of DC. Therefore, alignment among the State, sports institutions, and school institutions is essential for developing specific rules so that athletes make the most of their sporting condition without losing sight of school/academic opportunities.